Stability analysis and compensation technique for low-voltage regulated cascode transimpedance amplifier. (January 2018) - Abdollahi, Behnam; Mesgari, Baset; Saeedi, Saeed; Nabavi, Abdolreza
Abstract: Stability of low voltage regulated cascode (RGC) transimpedance amplifier (TIA) with level shifter path is analyzed and criterions for a well-behaved time response are derived. It is shown that there is a trade-off between the amplifier bandwidth and stability in this topology. Improving bandwidth by increasing transconductance of transistors leads to ringing in the step response of the amplifier and finally its instability. To add a degree of freedom to design of the low-voltage RGC circuit for high-speed optical receivers, a compensation technique is proposed in this paper and employed in a TIA circuit, designed in a 0.18 μm CMOS technology. Post layout simulation results show a gain of 52 dBΩ and bandwidth of 3 GHz in presence of a 2 pF photo-detector (PD) capacitance and with power consumption of 4.3 mW. The results show that the proposed technique enhances bandwidth of the low-voltage RGC circuit by about 40%, while preserving its stability and well-behaved time response.